2023
DOI: 10.3390/agriculture13091682
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Drip Irrigation Quota on Biochemical Activities and Yield-Related Traits in Different Drought-Tolerant Maize Varieties

Chen Xu,
Fei Li,
Yan Zhuang
et al.

Abstract: Drip irrigation has a close relationship with the growth and development of maize grains and yield formation in semiarid areas. To explore the response mechanism of grain yield formation to drip irrigation quotas, a 2-year pond planting experiment was conducted under controlled conditions, by using two maize varieties with differences in drought resistance as experimental materials. Six treatments were set up, including CK1 (drought-resistant variety, 500 mm), T1 (drought-resistant variety, 350 mm), T2 (drough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…GBSS contributes to amylose formation, while SSS and SBE mainly contribute to amylopectin formation [ 21 ]. Some research has shown that increasing these enzyme activities through crop cultivation methods like fertilization, irrigation, and chemical control can promote starch accumulation, resulting in higher grain weight [ 22 , 23 ]. Clearly, variations in these enzyme activities directly affect grain filling and weight by regulating starch accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…GBSS contributes to amylose formation, while SSS and SBE mainly contribute to amylopectin formation [ 21 ]. Some research has shown that increasing these enzyme activities through crop cultivation methods like fertilization, irrigation, and chemical control can promote starch accumulation, resulting in higher grain weight [ 22 , 23 ]. Clearly, variations in these enzyme activities directly affect grain filling and weight by regulating starch accumulation.…”
Section: Introductionmentioning
confidence: 99%